Gaps and opportunities for cervical cancer prevention, diagnosis, treatment and care: evidence from midterm review of the Zimbabwe cervical Cancer prevention and control strategy (2016-2020) - Oscar Tapera; Anna M. Nyakabau; Ndabaningi Simango; Bothwell T. Guzha; Shamiso Jombo-Nyakuwa; Eunice Takawira; Angeline Mapanga; Davidzoyashe Makosa; Bernard Madzima (BMC, 2021)
Abstract Background Cervical cancer is the fourth most common cancer amongst women globally and it accounts for the majority of cancer deaths among females in Zimbabwe. The objective of this midterm review analysis was to identify the gaps and opportunities for cervical cancer prevention, diagnosis, treatment, and care to inform the next cervical cancer strategy in Zimbabwe. Methods A mixed methods approach was used for the midterm review. Secondary data was collected from programme documents, published and grey literature. Primary data was collected in six provinces through key informant interviews with officials and focus group discussions with beneficiaries. After data analysis, a draft report was presented to a technical working group to validate the findings and to fill in any gaps. Results This midterm review revealed a myriad of gaps of the strategy particularly in diagnosis, treatment and care of cervical cancer and the primary focus was on secondary prevention. There was no data to quantify the level of awareness and advocacy for cervical cancer prevention. Our results revealed that there was no data on the proportion of women who ever tested for cervical cancer which existed nationally. Our findings suggest that some health facilities were screening women above 50 years old using VIAC, which is an inappropriate approach for those women. Quality control of VIAC and treatment of precancers were not part of the strategy. Pathological services were not efficient and effective due to lack of resources and additionally data on investigations were not routinely collected and available at the national level. Other gaps identified were limited funding, human resources, equipment, and commodities as well as lack of leadership at the national level to coordinate the various components of the cervical cancer programme. There are also numerous opportunities identified to build upon some successes realized to date. Conclusions Our findings emphasized the importance of effective and holistic planning in cervical cancer screening programmes in low-resource settings. In addition, huge investments are required in cervical cancer programmes and governments need to take centre role in mobilizing the requisite resources.